Media, Conflicts and the National Security Question Communicating (In)security in Nigeria, West Africa and the Sahel - Adeniyi, Abiodun; Obi, Paul A.; Usman, Sani K.; Yusuf, Ibrahim U. (Springer Nature Switzerland : Imprint: Palgrave Macmillan, 2025)
XXIX, 421 p. 4 illus., 2 illus. in color.